(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Concrete generally used in any types of construction work. Concrete is the mixture of cementsand and aggregate this is a basic definition of concrete but day by day new experiment have going on.Various alternate materials we used in construction industry. Concrete ingredients is different materiallike binding material (cement+ fly ash), fine aggregate, coarse aggregate and water. Today constructioncost is very high with using conventional materials due to unavailability of natural materials. Thisproblem can be solved by total replacement of concrete with different material which is not convenient interms of required properties. Due to this limitation of unavailability of material which plays the vital roleof concrete we have only choice of partial replacement of concrete ingredients by waste materials.Approx. Six billion tons of cement was consumed globally in 2023 based on survey of world coalassociation and also cement production emits CO2 in to the atmosphere which is harmful to the nature.If we can partially replace the construction materials with the material with desirable properties then wecan save natural material and reduce emission of CO2 in to the atmosphere. So use of this wastematerial in concrete is cost effective as well as environment friendly way to disposal of waste. Theprimary objective of this study is to select the waste material which gives desirable properties withconcrete. This study includes previous investigation done on the mechanical and chemical properties ofconcrete produced using partial replacement of construction materials by waste materials.